2018
DOI: 10.1002/asia.201801555
|View full text |Cite
|
Sign up to set email alerts
|

Tripyridine‐Derivative‐Derived Semiconducting Iodo‐Argentate/Cuprate Hybrids with Excellent Visible‐Light‐Induced Photocatalytic Performance

Abstract: Through regulating the pH values, a series of iodo‐argentate/cuprate hybrids, [Me3(4‐TPT)]4[Ag6I18] (1, Me3(4‐TPT)=N,N′,N′′‐trimethyl‐2,4,6‐tris(4‐pyridyl)‐1,3,5‐triazine), [Me3(4‐TPT)][M5I8] (M=Ag/2, Cu/2 a), [Me3(3‐TPT)][M5I8] (Me3(3‐TPT)=N,N′,N′′‐trimethyl‐2,4,6‐tris(3‐pyridyl)‐1,3,5‐triazine, M=Ag/3, Cu/4), which exhibit adjustable structural variations with different dimensional structures, have been obtained under solvothermal conditions. They are directed by two types of in situ N‐alkylation TPT‐derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 83 publications
(147 reference statements)
0
23
0
Order By: Relevance
“…Recently, our research focusing on the systematic exploration of halometallates using the conjugated polypyridine derivatives as SDAs has made some progress . These previous study indicated that N ‐alkylation conjugated polypyridine cations as SDAs and electron acceptors can effectively decrease the band gap and accordingly increase the absorption of the visible light of the resultant materials.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, our research focusing on the systematic exploration of halometallates using the conjugated polypyridine derivatives as SDAs has made some progress . These previous study indicated that N ‐alkylation conjugated polypyridine cations as SDAs and electron acceptors can effectively decrease the band gap and accordingly increase the absorption of the visible light of the resultant materials.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the N ‐alkylation reaction of bpanth and CH 3 OH can also be further verified by the characteristic absorption peaks of −CH 3 group in IR spectra (Figure S3). The absorption bands around 2914 and 1390 cm −1 are directly related to the stretching vibrations and in‐plane bending vibration of C−H bond of −CH 3 unit, respectively, indicating that bpanth has been methylated and further directing the resultant materials …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations